Pengaruh Brand Image Dan Perceived Price Terhadap Purchase Intention Produk Sedap Kecap Manis Di Kota Bekasi - Galih Pratama; Redjeki Agoestyowati (JAMBIS : Jurnal Administrasi Bisnis, 2025)
In the sweet soy sauce industry, competition among brands has become increasingly intense. One wellknown product among Indonesian consumers is Sedap Sweet Soy Sauce, which competes directly withbrands such as ABC, Bango, and Indofood. Although widely recognized nationwide, consumerpurchase intention toward Sedap Sweet Soy Sauce in urban areas like Bekasi City displays uniquedynamics. This study aimed to examine the influence of brand image and perceived price on thepurchase intention of Sedap Sweet Soy Sauce in Bekasi City. A quantitative research approach wasemployed using a descriptive research method. The population consisted of all consumers of SedapSweet Soy Sauce in Bekasi City. Data were collected through questionnaires and observations. Thesampling technique followed Hair’s recommendation, with a total sample of 110 respondents. Datawere analyzed using multiple linear regression with IBM SPSS Statistics version 29.0. The findingsrevealed that brand image had a significant influence on purchase intention, accounting for 64.3%.Perceived price also had a significant positive influence, contributing 46.2%. Furthermore, brand imageand perceived price simultaneously exerted a significant positive influence on purchase intention, with acombined contribution of 67.3%, while the remaining 32.7% was explained by other variables notexamined in this study.Keywords: Brand Image, Perceived Price, Purchase Intention